Cooling Potential Of Passive Roof Treatments On The Concrete Flat Roof In Penang, Malaysia - Ismail, Asmat (2013)
The rise in global temperature due to global warming has a major impact on the environment and building occupants. The higher concentration of greenhouse gases, in the atmosphere, especially carbon dioxide (CO2), is thought to be the reason for this phenomenon. Higher outdoor and indoor air temperatures lead to higher energy consumption in buildings due to the excessive use of air conditioning and other mechanical ventilation systems. Implementing passive cooling systems into the building elements can be a promising way to overcome this problem. From the literature, passive cooling techniques using green roof, double roof, and reflective roof (white roof) technologies could have a positive impact on the building environment. However, the cooling potential of these technologies varies depending on their design and the type of climate. Therefore, in order to investigate the effectiveness of these technologies in the Malaysian climate, a comparative study of these passive cooling technologies is carried out in this research. A series of field experimental studies has been carried out on a real building, i.e., on the flat roof of a single-storey residential building, in the actual weather conditions. The indoor and outdoor environments were monitored in this research to evaluate the most effective passive cooling roof treatment between the potted plant green roof (roof with potted plants), double roof (roof with 6 inches ventilated air gap) and white roof. The results show a significant cooling effect for all strategies. The highest indoor-outdoor air temperature difference, which is the main criteria in determining the cooling effect, is taken into account in this research.